ANALISIS IMPLEMENTASI PENCEGAHAN TINDAK PIDANA KORUPSI PENGELOLAAN KEUANGAN APBN PADA LINGKUNGAN PENGADILAN TINGGI YOGYAKARTA - Toni Subagyo; Yanto (Kajian Hukum, 2025)
The phenomenon underlying this research is the prevalence of criminal corruption cases involving the management of APBN in various government institutions, including judicial bodies. Despite the High Court of Yogyakarta implementing various preventive measures, challenges persist, both in terms of policy implementation and internal factors affecting the effectiveness of prevention. This study employs a normative research method with a juridical-normative approach, encompassing both statutory and conceptual perspectives. Data analysis is carried out by examining relevant data related to the research problem, and then clearly depicting the actual state of facts based on logical reasoning. The effectiveness of anti-corruption measures within the High Court of Yogyakarta can be considered to be functioning well. This is attributed to the goodwill of the High Court's leadership, which plays a crucial role in creating a proper and compliant financial management environment. With the commitment and goodwill from the leadership, it is hoped that the management of APBN within the High Court of Yogyakarta can avoid misuse of authority and criminal corruption.